Acetylcholine: The Master Messenger of the Nervous System - ChouhanAnju*, ChouhanAnju* (Asian Journal of Biological and Life Sciences, 2026)
Acetylcholine is the major neurotransmitter, whose role in mediating synaptic interactions between neurones in the central nervous system as well as in the peripheral nervous system is well characterized. In human beings acetylcholine system regulates multiple physiological processes not only in neuronal tissues but also in nonneuronal tissues. However, since the concept of the “nonneuronal cholinergic system” has been proposed, the role of the acetylcholine system in nonneuronal tissues has received increasing attention. A growing body of research shows that the acetylcholine system also participates in modulating inflammatory responses, regulating contraction and mucus secretion of respiratory tracts, and influencing the metastasis and invasion of lung cancer. In addition, the susceptibility and severity of respiratory tract infections caused by pathogens such as Mycobacterium tuberculosis and the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) can also correlate with the regulation of the acetylcholine system. So, acetylcholine as an excitatory neurotransmitter not only affect many neuronal processes, development of nervous system, plasticity of nervous system, cope up with stress, neuroprotection but it also influences other systems respiratory, cardiovascular, gastrointestinal as well.
Keywords: Acetylcholine; Nonneuronal Cholinergic System; Central Nervous System; Peripheral; Nervous System